Burden of HIV-associated histoplasmosis compared with tuberculosis in Latin America: a modelling study. Issue 10 (October 2018) - Adenis, Antoine A; Valdes, Audrey; Cropet, Claire; McCotter, Orion Z; Derado, Gordana; Couppie, Pierre; Chiller, Tom; Nacher, Mathieu
Summary: Background: Fungal infections remain a major contributor to the opportunistic infections that affect people living with HIV. Among them, histoplasmosis is considered neglected, often being misdiagnosed as tuberculosis, and is responsible for numerous deaths in Latin America. The objective of this study was to estimate the burden of HIV-associated histoplasmosis compared with tuberculosis in Latin American countries. Methods: For this modelling study, we estimated prevalence of previous exposure to Histoplasma capsulatum, HIV-associated histoplasmosis annual incidence, and number of deaths in 2012 in Latin American countries based on historical histoplasmin skin test studies in the general population, with an antigen dilution level of more than 1/10. Studies were identified in a literature search. Data on HIV-associated tuberculosis were extracted from the WHO notifications and outcomes tables and data on people living with HIV were extracted from the UNAIDS report for the year 2012. We systematically propagated uncertainty throughout all the steps of the estimation process. Findings: Among 1310 articles identified as of June 1, 2015, 24 articles were included in the study, representing 129 histoplasmin skin test studies led in the general population of Latin American countries. For the year 2012, we estimated a range of 6710 (95% CI 5680–7867) to 15 657 (13 254–18 357) cases of symptomatic HIV-associated histoplasmosis in Latin America. Hotspot areas for histoplasmosis prevalence (>30%) and incidence (>1·5 cases per 100 people living with HIV) were Central America, the northernmost part of South America, and Argentina. According to realistic scenarios, we estimated a range of 671 (95% CI 568–787) to 9394 (7952–11 014) deaths related to histoplasmosis, compared with 5062 (3777–6405) deaths related to tuberculosis reported in Latin America. Interpretation: Our estimates of histoplasmosis incidence and deaths are high and consistent with published data. For the first time, the burden of histoplasmosis is estimated to be equivalent in incidence and even higher in deaths when compared with tuberculosis among people living with HIV in Latin America. Funding: None.